ViRBase v3.0: a virus and host ncRNA-associated interaction repository with increased coverage and annotation. Issue Volume 50:Issue D1(2022) (1st November 2021) - Cheng, Jun; Lin, Yunqing; Xu, Linfu; Chen, Kechen; Li, Qi; Xu, Kaixin; Ning, Lin; Kang, Juanjuan; Cui, Tianyu; Huang, Yan; Zhao, Xiaoyang; Wang, Dong; et al.
Abstract: As a means to aid in the investigation of viral infection mechanisms and identification of more effective antivirus targets, the availability of a source which continually collects and updates information on the virus and host ncRNA-associated interaction resources is essential. Here, we update the ViRBase database to version 3.0 (http://www.virbase.org/ or http://www.rna-society.org/virbase/ ). This update represents a major revision: (i) the total number of interaction entries is now greater than 820, 000, an approximately 70-fold increment, involving 116 virus and 36 host organisms, (ii) it supplements and provides more details on RNA annotations (including RNA editing, RNA localization and RNA modification), ncRNA SNP and ncRNA-drug related information and (iii) it provides two additional tools for predicting binding sites (IntaRNA and PRIdictor), a visual plug-in to display interactions and a website which is optimized for more practical and user-friendly operation. Overall, ViRBase v3.0 provides a more comprehensive resource for virus and host ncRNA-associated interactions enabling researchers a more effective means for investigation of viral infections.